2019
DOI: 10.1590/2179-8087.033918
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grazing on the Plant Community of a Southern Brazilian Swamp

Abstract: Swamps have high biological diversity and are the largest producers of biomass. However, such ecosystems are threatened by human activities. This study analyzes the plant community structure of two swamp sites, with and without grazing. A total of 200 sample units with 0.25 m 2 were distributed every 13 m to determine diversity, the Importance Value Index (IVI), and coverage. Fifty species and 18 families were recorded. Luziola peruviana Juss. ex. JF Gmel had the highest IVI, accounting for 62.57% of the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Since species density, frequency and dominance comprised IVI are sensitive indicators to anthropogenic actives 26 , 27 . Reaction of species to human exploitation can be revealed with comparing IVI with and without exploiting 28 , 29 . Relative loss (RL) index was measured to assess ecological situation of medicinal plants under both nomadic and sedentary pastoral system using changes IVI.…”
Section: Methodsmentioning
confidence: 99%
“…Since species density, frequency and dominance comprised IVI are sensitive indicators to anthropogenic actives 26 , 27 . Reaction of species to human exploitation can be revealed with comparing IVI with and without exploiting 28 , 29 . Relative loss (RL) index was measured to assess ecological situation of medicinal plants under both nomadic and sedentary pastoral system using changes IVI.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the results of community stability calculations also indicated that the community composition at the MG site was more stable than that at the HG site (A lower score indicates a more stable community; therefore, the MG plant community had the highest stability, Supplementary Table 1). In contrast, Spellmeier et al (2019) in swamps of southwestern Brazil showed that grazing reduced plant species richness. Spellmeier et al (2019) selected a test site with naturally high plant richness that was in its native state; the data showed that the species count at that site under non-degraded conditions was much higher than that in the C. meyeriana meadow considered in this study.…”
Section: Effects Of Utilization Mode On Grassland Plant Communitiesmentioning
confidence: 79%
“…In contrast, Spellmeier et al (2019) in swamps of southwestern Brazil showed that grazing reduced plant species richness. Spellmeier et al (2019) selected a test site with naturally high plant richness that was in its native state; the data showed that the species count at that site under non-degraded conditions was much higher than that in the C. meyeriana meadow considered in this study. In conclusion, our experimental results indicated that UN (enclosure) is not the most appropriate management method for meadows in the long run (Sun et al, 2020).…”
Section: Effects Of Utilization Mode On Grassland Plant Communitiesmentioning
confidence: 79%